2004
DOI: 10.1021/bi0493618
|View full text |Cite
|
Sign up to set email alerts
|

Nikkomycin Biosynthesis:  Formation of a 4-Electron Oxidation Product during Turnover of NikD with Its Physiological Substrate

Abstract: Nikkomycins are peptidyl nucleoside antibiotics that act as therapeutic antifungal agents in humans and easily degraded insecticides in agriculture. The nikkomycin peptidyl moiety contains a pyridyl residue derived from L-lysine. The first step in peptidyl biosynthesis is an aminotransferase-catalyzed reaction that converts L-lysine to Delta(1)- or Delta(2)-piperideine-2-carboxylate (P2C). Spectral, chromatographic, and kinetic analyses show that the aerobic reaction of nikD with P2C results in the stoichiomet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
50
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(51 citation statements)
references
References 28 publications
1
50
0
Order By: Relevance
“…Anion exchange HPLC analyses were conducted by using isocratic elution at a flow rate of 1.4 ml/min (method 1) or 1.2 mL/min (method 2). Method 1 corresponds to the previously described high resolution protocol for separation of positional isomers of picolinate (6). The elution solvent for method 2 was prepared by mixing (v/v) 1 part of 25 mM ammonium carbonate pH 10.3 with 1 part of 50% methanol in water (v/v).…”
Section: Chromatography and Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation
“…Anion exchange HPLC analyses were conducted by using isocratic elution at a flow rate of 1.4 ml/min (method 1) or 1.2 mL/min (method 2). Method 1 corresponds to the previously described high resolution protocol for separation of positional isomers of picolinate (6). The elution solvent for method 2 was prepared by mixing (v/v) 1 part of 25 mM ammonium carbonate pH 10.3 with 1 part of 50% methanol in water (v/v).…”
Section: Chromatography and Spectroscopymentioning
confidence: 99%
“…Subsequent conversion of DHP to picolinate appears to proceed without release of the labile DHP intermediate into solution (5,6).…”
mentioning
confidence: 99%
“…Following the cloning of the entire set of structural genes involved in nikkomycin biosynthesis, [6] the enzymatic steps leading to the 4-formyl-4-imidazolin-2-one base were investigated in some detail. [7][8][9] The peptidyl moiety is synthesized by eleven enzymatic reactions, of which only two have been investigated in depth. [10,11] The aminohexuronic acid is introduced into the nikkomycin skeleton by the transfer of 5-phosphoribosyl-1-pyrophosphate to the nucleobase (uracil or 4-formyl-4-imidazolin-2-one) followed by addition of an enolpyruvyl moiety from phosphoenolpyruvate (PEP), supposedly to the 5'-hydroxyl group of the ribose.…”
mentioning
confidence: 99%
“…Previous studies demonstrated that a L-lysine 2-aminotransferase catalyzes the initial reaction from L-lysine to piperideine-2-carboxylate (P2C) in HPHT formation [9]. A monomeric sarcosine oxidases was found to be responsible for the conversion of P2C to picolinic acid, which was activated by a picolinate-CoA ligase to continue subsequent reactions [4,10]. …”
Section: Introductionmentioning
confidence: 99%